Intra-Couple (Dis)Similarity in Gender Role Attitudes and the Transition to Parenthood in Germany. (25th June 2020) - Hudde, Ansgar; Engelhardt, Henriette
Abstract: This paper tests whether couples in which partners hold dissimilar gender role attitudes are less likely to have a first child together compared to couples in which both partners share similar attitudes. The study contributes to micro-level research on gender role attitudes and fertility, which has examined the content of one partner's attitudes, but not the fit of both partners' views. We analyse unique panel data from the German Family Panel (pairfam) collected between 2008 and 2017, which includes information on the attitudes of both partners in a couple. Results show that couples whose members have dissimilar gender role attitudes are substantially and significantly less likely to have a child together over time. This observation holds independently of both partners' individual attitudes and holds against a number of robustness checks.